Atmospheric Ice Loading and its Impact on Natural Frequencies of Wind Turbines. Issue 1 (February 2015) - Alsabagh, Abdel Salam Y.; Xu, Yigeng; Virk, Muhammad S.; Badran, Omar
Wind energy is a promising way in the middle of growing demand for clean energy in high north, where atmospheric icing is a hazard for safe operations of wind turbines. In this research work, the vibrational effects due to atmospheric ice accretion on a multi megawatt large wind turbine are numerically investigated using a finite element based approach. Three different icing scenarios were addressed and accreted on-blade ice mass was calculated analytically based upon ISO 95214 standards. Special attentions are given to the first natural frequency of the wind turbine blade and its interaction when the exciting frequency approaches the natural frequency of the wind turbine tower. Results show variations of natural frequencies due to different accreted icing loads scenarios, which may have different implications to the integrity of the structure.